Regulation of Milk Fat Synthesis: Key Genes and Microbial Functions - Ye Yu; Runqi Fu; Chunjia Jin; Huan Gao; Lin Han; Binlong Fu; Min Qi; Qian Li; Zhuo Suo; Jing Leng (Microorganisms)
Milk is rich in a variety of essential nutrients, including fats, proteins, and trace elements that are important for human health. In particular, milk fat has an alleviating effect on diseases such as heart disease and diabetes. Fatty acids, the basic units of milk fat, play an important role in many biological reactions in the body, including the involvement of glycerophospholipids and sphingolipids in the formation of cell membranes. However, milk fat synthesis is a complex biological process involving multiple organs and tissues, and how to improve milk fat of dairy cows has been a hot research issue in the industry. There exists a close relationship between milk fat synthesis, genes, and microbial functions, as a result of the organic integration between the different tissues of the cow’s organism and the external environment. This review paper aims (1) to highlight the synthesis and regulation of milk fat by the first and second genomes (gastrointestinal microbial genome) and (2) to discuss the effects of ruminal microorganisms and host metabolites on milk fat synthesis. Through exploring the interactions between the first and second genomes, and discovering the relationship between microbial and host metabolite in the milk fat synthesis pathway, it may become a new direction for future research on the mechanism of milk fat synthesis in dairy cows.